Perbedaan As-Sunnah Al-Risala Dan As-Sunnah Al-Nabawiyah: Analisis Pemikiran Muhammad Syahrur Dalam Pemahaman Hukum Islam - Hulliyatus Saniyah; Muhammad Sahlan (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This research aims to examine the differences between As-Sunnah Ar-Risala and As-Sunnah Al-Nabawiyah according to Muhammad Syahrur. Syahrur is a contemporary thinker who offers a concept that differentiates between sunnah which is divine and absolute and sunnah which is tied to social context. This research uses a qualitative approach or library research method, with primary sources in the form of books and articles about Muhammad Syahrur. Then Syahrur classified the sunnah into three approaches, namely: textual, conceptual and contextual. This approach opens up insight into understanding hadith flexibly and relevantly in today's modern context. This research shows that As-Sunnah Ar-Risala is a divine decree that cannot be changed and must be obeyed. Meanwhile, As-Sunnah Al-Nabawoyah is more flexible and contextual according to social changes. Seeing this, Muhammad Syahrur is trying to encourage a more critical and dynamic understanding of the teachings of the Prophet Muhammad SAW so that they remain relevant in modern times.